Relationship between 6‐ and 9‐month progression‐free survival and overall survival in patients with metastatic urothelial cancer treated with first‐line cisplatin‐based chemotherapy. Issue 16 (29th May 2013) - Galsky, Matthew D.; Krege, Susan; Lin, Chia‐Chi; Hahn, Noah; Ecke, Thorsten; Moshier, Erin; Sonpavde, Guru; Godbold, James; Oh, William K.; Bamias, Aristotle
<x xml:space="preserve">Abstract</x> BACKGROUND Use of progression‐free survival (PFS) as a clinical trial endpoint in first‐line treatment of patients with metastatic urothelial carcinoma (UC) is attractive, but would be enhanced by establishing a correlation between PFS and overall survival (OS). METHODS Data was pooled from 7 phase 2 and 3 trials evaluating cisplatin‐based chemotherapy in metastatic UC. An independent cohort of patients enrolled on a phase 3 trial was used for external validation. Landmark analyses for progression at 6 and 9 months after treatment initiation were performed to minimize lead‐time bias. A proportional hazards model was used to assess the utility of PFS for predicting OS. RESULTS A total of 364 patients were included in the initial cohort. The median PFS was 8.21 months (95% confidence interval = 7.43, 8.39) and the median OS was 13.50 months (95% confidence interval = 11.80, 15.67). In the landmark analysis, the median OS for patients who progressed at 6 months was 3.87 months compared with 15.06 months for those patients who did not progress (P < .0001) and the median OS for patients who progressed at 9 months was 5.65 months compared with 21.39 months for those patients who did not progress (P < .0001). A Fleischer model demonstrated a statistically significant dependent correlation between PFS and OS. The findings were externally validated in an independent cohort. CONCLUSIONS PFS at 6 and 9 months predicted OS in this analysis of patients with metastatic UC treated with first‐line cisplatin‐based chemotherapy and could potentially serve as endpoints in (randomized) phase 2 trials to screen the activity of novel regimens. Cancer 2013;119:3020—3026. © 2013 American Cancer Society.